1983
DOI: 10.1093/jn/113.2.412
|View full text |Cite
|
Sign up to set email alerts
|

Digestion and Absorption of NAD by the Small Intestine of the Rat

Abstract: A number of preparations of varying complexity have been used in an effort to elucidate the reactions by which NAD is hydrolyzed to nicotinamide during intestinal digestion. NAD labeled with 14C in the adenine or pyridine moiety was the substrate used with perfused rat intestine, live rats, perfused live rats, with collection of portal flow, intestinal contents, mucosal tissue, or pancreatic juice. The conclusions reached are that a pyrophosphatase present in the intestinal juice and to a much lesser extent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 10 publications
1
33
0
Order By: Relevance
“…Gross and Henderson (1) revealed that NAD ϩ is efficiently digested in the small intestinal tract, producing Nam that is transported into the blood and distributed to various tissues. Nam in the circulation appears to take two metabolic pathways depending on the cellular conditions; Nam is reused for biosynthesis of NAD ϩ and NADH or it gives rise to some downstream metabolites whose physiological functions are not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gross and Henderson (1) revealed that NAD ϩ is efficiently digested in the small intestinal tract, producing Nam that is transported into the blood and distributed to various tissues. Nam in the circulation appears to take two metabolic pathways depending on the cellular conditions; Nam is reused for biosynthesis of NAD ϩ and NADH or it gives rise to some downstream metabolites whose physiological functions are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Excess Nam is converted into nicotinamide N -oxide (Nam N -oxide), N 1 -methylnicotinamide (MNA), N 1 -methyl-2-pyridone-5-carboxamide (2-Py), and N 1 -methyl-4-pyridone-3-carboxamide (4-Py) and these catabolites are excreted into urine in mice ( 3 ). It has been shown that orally taken NAD ϩ also supplies Nam, since NAD ϩ is metabolized to Nam in the small intestinal tract ( 1 ).…”
mentioning
confidence: 99%
“…Interestingly, niacin is found in maize but is not bioavailable unless given an alkali treatment, a process used in Aztec and Mesoamerican times termed nixtamalization (Gwirtz and Garcia-Casal, 2014). In animal products, and probably in all uncooked foods, the NAD + and NADP + cellular content accounts for much of their dietary niacin content (Gross and Henderson, 1983), yet, as exemplified above with corn nixtamalization, their bioavailability might be affected by food processing or cooking.…”
Section: Introductionmentioning
confidence: 99%
“…The latter was probably formed by the action of bacterial or mammalian nucleotidases (Pike & Brown, 1975). In rats formation of nicotinamide from brush-border-associated dinucleotides has also been reported (Gross & Henderson, 1983). Thus, it appears that the ruminant host has access to both nicotinic acid and nicotinamide to meet the specific requirements of individual organs (Giesecke, 1983).…”
Section: A B S O R P T I O N F R O M T H E S M a L L I N T E S T I N mentioning
confidence: 99%